Introduction: Enquiries into Contemporary Ritual Landscapes - Pirjo Kristiina Virtanen; Eleonora A. Lundell; Marja-Liisa Honkasalo (Estonian National Museum, 2022)
‘Landscape’ and ‘ritual’ have been largely discussed in the social and human sciences, although their inter-relatedness has gained little scholarly attention. Drawing on earlier studies of ritual and landscape, as well as the authors’ own ethnographic works, ‘ritual landscape’ is suggested here as a useful analytical tool with which to understand how landscapes are produced, and how they, in their turn, produce certain types of being. ‘Ritual landscape’ recognises different modalities of agency, power-relation, knowledge, emotion, and movement. The article shows how the subjectivity of other-than-human beings such as ancestors, earth formations, land, animals, plants and, in general, materiality of ritual contexts, shape landscapes. We argue that ways of perceiving landscape includes a number of material and immaterial aspects indicated by ways of moving through landscapes and interacting with different human and non-human subjects that come to inhabit the world, creating relations and producing agentive ensembles and complexes.
KEYWORDS: ritual landscape • non-human agency • materiality • immateriality • belonging • relationality